Exportações fictícias como fonte de sonegação fiscal no estado do Ceará no biênio 2004-2005 - Bastos, Fernando José Cavalcante (2006)
With the advent of the global economy, companies considered this entire gap as an opportunity to expand their business to other countries and conquer the market for their products and consequently reach a sustainable growth. What happens is that not all the companies present an ethical behavior with their competitors practicing evasion of taxes in order to obtain more profits in their businesses. The taxes charged over the operation of merchandising circulation and over interstate and intermunicipal transportation service and taxes charged for communication (ICMS), which is of state competence. It is one of the favorite aims for the practice of fiscal evasion, for this is heaviest tribute on the prices of products. The most used practice of fiscal evasion of ICMS in the exportation operations is the fictitious exportation, which consists on the simulation of an exportation operation to cover a sales operation in the internal market. In one type of exportation, which is the case of indirect exportation, due to the fact that it involves more than one company, in most of the cases, two units of the Federation. Difficulties are created for fiscal taxation on the combat of the practice of fiscal evasion. The fictitious exportation contributes on the decrease of the ICMS tax collection, generating a debit balance, which can be transferred to other companies, whether they belong to the same owner or not. The study was developed in the scope of the Foreign Commerce control Center in the Treasury Department of the State of Ceará and the study was held based on the executed fiscal audits held in the referred center, comprising the years of 2004 and 2005. 89 processes of exportation were analyzed and 115 credit transfers during this period, from the total of 98 processes of exportation and from 210 processes of credit transfer, with results being presented according to effectuated written charges, proving that the fictitious exportation is a relevant source of fiscal evasion in the state of Ceará.